Panorama of Nome, October 10, 1908 (4th in series) - Nowell, Frank H., 1864-1950 (1908)
Section of 5-part panorama: Nowell 6670, 6671, 6672, 6673, 6674. Caption on image: 6673 On verso of image: Panorama of Nome, 10-10-08, #4 in series To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number